2017
DOI: 10.1093/nar/gkx633
|View full text |Cite
|
Sign up to set email alerts
|

Engineering human PrimPol into an efficient RNA-dependent-DNA primase/polymerase

Abstract: We have developed a straightforward fluorometric assay to measure primase-polymerase activity of human PrimPol (HsPrimPol). The sensitivity of this procedure uncovered a novel RNA-dependent DNA priming-polymerization activity (RdDP) of this enzyme. In an attempt to enhance HsPrimPol RdDP activity, we constructed a smart mutant library guided by prior sequence-function analysis, and tested this library in an adapted screening platform of our fluorometric assay. After screening less than 500 variants, we found a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…For this aim, we attemped to establish an assay to quantify RNA synthesis activity as the relative increase in fluorescence emitted by SYBR Green II dye after binding to dsRNA. This procedure was adapted from methods previously described to detect dsDNA synthesis by the human primase-polymerase PrimPol 38 . We anticipated that binding of this intercalating agent to dsRNA generated by ZIKV RdRp polymerization activity would lead to an increase in the emitted fluorescence.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For this aim, we attemped to establish an assay to quantify RNA synthesis activity as the relative increase in fluorescence emitted by SYBR Green II dye after binding to dsRNA. This procedure was adapted from methods previously described to detect dsDNA synthesis by the human primase-polymerase PrimPol 38 . We anticipated that binding of this intercalating agent to dsRNA generated by ZIKV RdRp polymerization activity would lead to an increase in the emitted fluorescence.…”
Section: Resultsmentioning
confidence: 99%
“…S1). Previous studies have documented that an excess of SYBR Green I, chemically related to SYBR Green II, can inhibit other polymerase activities, such as those of Taq polymerase 43 or human PrimPol 38 . Our resulted suggested that SYBR Green II acts as an inhibitor of ZIKV RdRp activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the Y89D mutation appears to be structurally conservative, explaining the moderate effect of this alteration on PrimPol in vitro activities and the absence of an effect on the tested PrimPol in vivo activities. Interestingly, a single mutation of Tyr 89 to Arg (Y89R), a change that is invariantly present in the WxRY motif of plant PrimPols (see Supplementary Figure S1 ), enhanced the capacity of human PrimPol as an efficient RNA-dependent-DNA primase/polymerase ( 34 ). Strikingly, this randomly selected mutation (Y89R) displayed an increased stabilization of the preternary complex (protein:template DNA:incoming nucleotide), the specific step preceding dimer formation.…”
Section: Resultsmentioning
confidence: 99%
“…Although partial kinetic characterizations have been reported [23,27,28], a complete kinetic pathway of PrimPol-mediated DNA elongation and the rate-limiting step(s) of the reaction are unknown. Such information is not only fundamental for further understanding the enzymatic activities of PrimPol and other primase-polymerases, but also useful for exploring novel approaches to modulate PrimPol's activities for biotechnological or therapeutic applications [25,29,30]. In this study, we conducted in-depth kinetic analyses and computer simulations to dissect the elemental steps of PrimPol's DNA polymerase activity.…”
Section: Introductionmentioning
confidence: 99%